UPAYA PENINGKATAN DAYA TARIK WISATA BERBASIS EDUKASI DI TAMAN BUNGA OKURA - Kamilah, Faizah; Khairani, Zulia; Soviyanti, Efrita (Komunitas Manajemen Kompetitif, 2024)
This community service activity aims to provide knowledge about how to increase education-based tourist attraction so that visitors are more interested in seeing and finally decide to visit the tourist attraction.The method of this community service activity uses the lecture method, as well as questions and answers. The lecture method is used to convey general knowledge about what efforts might be made to increase tourist attractiveness and increase the number of visitors. Questions and answers are used to complement things that have not been accommodated by the lecture method. This training involved lecturers from the Department of Accounting and Management in collaboration with the okura flower garden group in rumbai barat village as the target subjects. Keywords: education, tourists and tourism